The Imposition of Digital Taxes in E-commerce - Sari Ramadhanti; Tjip Ismail (Fakultas Hukum, Universitas Warmadewa, 2023)
In the business world, information and communication technology offers an advantage in terms of supporting online commercial transactions, also known as Electronic System-Based Trade (E-commerce). Tax is one of the most significant governmental revenues for national development. It aims to increase people's prosperity and welfare, which requires a lot of economic resources. The objectives of this paper is to learn more about the regulations surrounding Digital Tax in e-commerce. This study's research method is a normative research method with a statutory approach. The the result reveal that there is no difference between e-commerce and traditional commerce in terms of the economic advantages provided; the only difference is in the method of completing transactions or the media used to meet sellers and customers. The criteria for Permanent Establishment (BUT) are being expanded with the goal of requiring corporations domiciled abroad to pay income tax even if they do not have a physical office in Indonesia.